P07.12 Factors influencing the detection of neisseria gonorrhoeae from the tonsils and posterior oropharynx. (13th September 2015) - Bissessor, M; Whiley, DM; Lee, DM; Snow, AF; Fairley, CK; Bradshaw, CS; Hocking, JS; Lahra, M; Peel, J; Chen, MY
Abstract : Background: Limited data exists on the specific anatomical areas within the pharynx from which Neisseria gonorrhoeae can be detected. We examined factors influencing the detection of gonorrhoea from the pharynx. Method: Men who had sex with men (MSM) diagnosed with pharyngeal gonorrhoea by culture were recalled for repeat swabbing 7 days later: firstly from both tonsils then, using separate swabs, from the posterior oropharynx. These were tested for N. gonorrhoeae using culture and real-time PCR targeting the gonococcal porA pseudogene and multi-copy opa genes. Cycle threshold (Ct) values obtained were used as semi-quantitative measures of gonococcal DNA. Sampling adequacy was assessed using a real-time PCR for human endogenous retrovirus 3 (ERV3). Results: 100 MSM with culture positive pharyngeal gonorrhoea were included. Isolation rates by culture from the tonsils and posterior oropharynx were 62% and 52% respectively (p = 0.041). PCR was significantly more sensitive than culture at both the tonsils (84% vs. 62%; p < 0.001) and oropharynx (81% vs. 52%; p < 0.001). Culture positivity was greater with higher gonococcal DNA loads at both the tonsils (p = 0.001) and oropharynx (p < 0.001). At the oropharynx, higher ERV3 DNA load was associated with improved gonococcal detection using culture (p = 0.013) as well as PCR (p = 0.045). At the tonsils, higher ERV3 DNA load was associated with improved gonococcal detection by PCR (p = 0.040). Conclusion: Neisseria gonorrhoeae can be cultured from the tonsils as well as the posterior oropharynx with greater isolation rates where gonococcal loads are higher. While PCR is substantially more sensitive than culture at each site, like culture, PCR is dependent on the adequacy of sampling. Disclosure of interest statement: None to disclose.